Analysis of 5G-Enabled Internet of Things (IoT) with AI: Enabling Smart and Connected Environments - Joe Laksamana Silitonga; Rijois I. E. Saragih (International Journal of Information System and Innovative Technology, 2023)
The convergence of 5G technology and artificial intelligence (AI) has the potential to reshape the landscape of the Internet of Things (IoT), paving the way for innovative applications in smart and con-nected environments. This research paper explores the synergy be-tween 5G and AI in the context of IoT, focusing on the transforma-tive impact on various sectors such as healthcare, industrial auto-mation, and smart cities. Through a comprehensive review of exist-ing literature and empirical analysis, this paper highlights the key challenges, opportunities, and technical advancements that arise when integrating 5G and AI technologies within IoT ecosystems. The study contributes to a deeper understanding of the implications of this convergence and offers insights into the future direction of research and development in this dynamic field